ANALISIS UNGKAPAN GANBARE DITINJAU DARI SEGI SOSIOLINGUISTIK - Parlani, Tri Yeni Putri; Budiani, Dini; Aibonotika, Arza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:This research aimed at finding out variation of word form of ganbare expression which is used by Japanese society. The subject in this research was ganbare expression used in Japanese conversation sentences from Japanese dramas called Ichi Rittoru No Namida and Nihonjin No Shiranai Nihongo.The method of this research is literature method and descriptive method.The result shows that in social factor, the ganbare expressionis used from various professions. The ganbare expression used by people around adolescent to adult, when the listener around adolescent to elder. The ganbare expressioncan be used by male or female. Next in situation factor, the ganbare expression often appears in informal conversation.Keywords: Ganbare, Form, Social Factor, Situation Factor